Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1152/ajpheart.00980.2010
|View full text |Cite
|
Sign up to set email alerts
|

Altered membrane lipid domains limit pulmonary endothelial calcium entry following chronic hypoxia

Abstract: Agonist-induced Ca(2+) entry into the pulmonary endothelium depends on activation of both store-operated Ca(2+) (SOC) entry and receptor-operated Ca(2+) (ROC) entry. We previously reported that pulmonary endothelial cell SOC entry and ROC entry are reduced in chronic hypoxia (CH)-induced pulmonary hypertension. We hypothesized that diminished endothelial Ca(2+) entry following CH is due to derangement of caveolin-1 (cav-1) containing cholesterol-enriched membrane domains important in agonist-induced Ca(2+) ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 28 publications
1
21
1
Order By: Relevance
“…Chronic hypoxia leads to a reduction in the membrane cholesterol and impairs agonist-induced Ca 2ϩ entry. The introduction of cell permeable CSD restores Ca 2ϩ entry in these cells (97). These observations indicate that caveolin-1 may be required for Ca 2ϩ entry in ECs for vasoactivity.…”
Section: Perturbation Of Ec Membranementioning
confidence: 65%
“…Chronic hypoxia leads to a reduction in the membrane cholesterol and impairs agonist-induced Ca 2ϩ entry. The introduction of cell permeable CSD restores Ca 2ϩ entry in these cells (97). These observations indicate that caveolin-1 may be required for Ca 2ϩ entry in ECs for vasoactivity.…”
Section: Perturbation Of Ec Membranementioning
confidence: 65%
“…We, therefore, postulated that TRPV4 channels in ECs from small PAs couple to novel physiological activators. Previous studies in large PAs revealed that endogenous purinergic receptor activator ATP increases endothelial Ca 2+ and causes endothelium‐dependent vasorelaxation 22, 23, 24, 46, 47. We, therefore, hypothesized that ATP dilates small PAs via activation of TRPV4 sparklets.…”
Section: Resultsmentioning
confidence: 93%
“…In this regard, purinergic receptor agonist ATP has been shown to increase endothelial Ca 2+ and cause vasodilation in large, conduit PAs. [22][23][24] ATP can be released into the circulation by ECs, smooth muscle cells (SMCs), and red blood cells. 25,26 Circulatory ATP may, therefore, serve as an important regulator of pulmonary vascular resistance.…”
mentioning
confidence: 99%
“…In coronary and other vascular smooth muscles, M␤CD treatment modifies ion channel function (BK Ca and Ca 2ϩ -activated Cl Ϫ currents) and receptordependent control of intracellular Ca 2ϩ concentration and vascular tone (40,47,51). M␤CD also modifies BK Ca currents in nonvascular smooth muscle (50), together with BK Ca activity (43) and agonist-mediated Ca 2ϩ entry (30) in the vascular endothelium. Interestingly, M␤CD treatment diminishes storeoperated Ca 2ϩ channel function (where the reduction in intracellular Ca 2ϩ stores activates Ca 2ϩ influx) and attenuates the hypertensive phenotype (associated with elevated caveolae/ caveolin levels) in pulmonary arteries from patients with idiopathic pulmonary arterial hypertension (33).…”
Section: Discussionmentioning
confidence: 99%
“…In other vascular smooth muscles, M␤CD enhances Ca 2ϩ -activated Cl Ϫ currents (51), and in uterine myocytes, M␤CD amplifies large-conductance Ca 2ϩ -activated K ϩ (BK Ca ) channel currents (50). In the vascular endothelium, M␤CD also enhances BK Ca activity to induce hyperpolarization (43) and represses agonist-mediated Ca 2ϩ entry (30).…”
mentioning
confidence: 99%